Regulasi Emosi Ditinjau Berdasarkan Jenis Kelamin pada Siswa SMP - Rica Widyadari; Yulia Fitriani (Departement of Mathematics Education, 2023)
Emotional regulation is an individual's ability to regulate feelings and physiological reactions and cognitions related to individual emotions. Individual goals have good emotional management skills, individual will experience a decrease in anger, anxiety and feelings of forgiveness as well as a significant decrease in depression. This study aims to determine differences in emotional regulation based on gender at SMPN 1 Tambun Utara. This study used a quantitative research method. The sample in this study totaled 70 students, namely 35 male students and 35 female students using the quota sampling technique. Data collection in this study used the emotion regulation scale which was modified by Fitriani and Alsa (2015). The research data were analyzed using the independent t test technique. The results show that there is no difference in emotional regulation between boys and girls in SMPN 1 Tambun Utara students.